STUDY OF THE BALANCE STABILITY OF YOGA EXERCISES PRACTITIONERS - Vladimir Angelov; Ognian Tishinov; Evald Albert (Journal of Applied Sports Sciences, 2017)
Yoga is an ancient system with complex effect on humans. The aim of this study was to determine the effect of the different structural groups of yoga exercises on the balance abilities of the practitioners. The object of the research was the balance stability. The subject of the study was the value and frequency fluctuations of COG during the execution of the control balance exercise. A contingent of the study was a group of 25 practitioners. The basic scientific method used for the realization of this research is the method of posturographic analysis. It allows to determine the dynamics of COG. The practical experiment includes measurments after every training impact with various structural groups of yoga exercises. The results concern the movements of the projection of COG. The collected data is presented through tables and graphs. The results reflect the dynamics of the COG during the execution of the balance exercise. Thus, this paper established the effect of the impact of various yogic exercises on the balance stability of the participants.